2016
DOI: 10.1159/000443435
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Cortisol and Chronic Kidney Disease in Patients with Essential Hypertension

Abstract: Background/Aims: Serum cortisol level is elevated in patients with essential hypertension. We aimed at investigating the association of serum cortisol levels with parameters of renal function in essential hypertension. Methods: One hundred and seventy-eight patients with essential hypertension participated in the study. Fasting serum samples were collected at 8:00 am. Renal function was measured as estimated glomerular filtration rate (eGFR) calculated by the Chronic Kidney Disease Epidemiology Collaboration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 26 publications
1
29
0
2
Order By: Relevance
“…Effective weight loss by lifestyle intervention and bariatric surgery were both associated with decreased cortisol levels in obese individuals 20 , 24 . Among subjects with similar BMI values, no significant difference was found in cortisol levels between patients with MetS and those without MetS 9 . Also, varied cortisol secretion patterns might present in patients in different age or development phase.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Effective weight loss by lifestyle intervention and bariatric surgery were both associated with decreased cortisol levels in obese individuals 20 , 24 . Among subjects with similar BMI values, no significant difference was found in cortisol levels between patients with MetS and those without MetS 9 . Also, varied cortisol secretion patterns might present in patients in different age or development phase.…”
Section: Discussionmentioning
confidence: 75%
“…A study in patients with essential hypertension demonstrated that serum cortisol level was negatively correlated with eGFR levels. But the researchers did not assess proteinuria 9 . In the present study, we found a significant positive correlation between serum cortisol and microalbuminuria, but not eGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal function parameters such as creatinine and cystatin C (eGFRcr-cys) are related to the high level of cortisol in subjects with SAH. 6,24 Recent studies have shown that deregulation of the HPA axis together with chronic stress increases the likelihood of SAH, leading to heart disease such as ischemia, a deficit in blood perfusion and stroke-related diseases. 22,23 In another investigation, it was suggested that healthy individuals with a genetic history of SAH have a marked increase in catecholamines and cortisol for stressors in relation to elevated plasma levels when compared to those with no parental history.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with end-stage renal disease also showed increased levels of pro-inflammatory cytokines (such as IL-1, IL-6, and tumor necrosis factor [TNF]-α), cortisol, and glucose [16][17][18]. Particularly, cortisol levels in serum were significantly higher in patients with impaired glomerular filtration rate [19].…”
Section: Discussionmentioning
confidence: 99%